Comparison of Adequacy of Anaesthesia (AoA) monitors with CONOX® monitor regarding sevoflurane consumption during routine general anaesthesia: A randomised clinical trial - Rajendran. Arulkumaran; Anusha Cherian; Aswini Kuberan; Prasanna Udupi Bidkar (Indian Journal of Anaesthesia)
Background and Aims: Adequacy of Anaesthesia (AoA) and CONOX® are combined monitors that assess levels of anaesthesia and analgesia and give a comprehensive score. No studies have measured and compared the total consumption of inhaled anaesthetic agents while using these monitors. We designed a study to compare AoA and CONOX in terms of sevoflurane usage, fentanyl usage and recovery from the effects of anaesthesia. Methods: A randomised trial was conducted in 58 patients. Group A (n = 31) patients were monitored with AoA, and Group C (n = 27) patients were monitored with CONOX. Sevoflurane was titrated to maintain a state entropy value of 40–60 in AoA and a Quantium consciousness index (qCON) value of 40–60 in CONOX. Similarly, fentanyl was titrated with bolus doses of 0.5 μg/kg to maintain a surgical pleth index value of 40–60 in AoA and Quantium noxious index (qNOX) value of 40–60 in CONOX. Intraoperative awareness was assessed postoperatively using a modified Brice questionnaire. The t-test or Chi-square test was used to compare the parameters between the groups. Results: Mean sevoflurane consumption was similar between AoA and CONOX groups [13.2 (standard deviation SD: 3.9) (95% confidence interval CI:11.8, 14.5) versus 14.4 (SD: 3.7) (95% CI: 13.0, 15.7) ml/h] (P = 0.236). Fentanyl usage was higher in the AoA group compared to the CONOX group [146.2 (SD: 34.28) (95% CI: 134.13, 158.26) versus 128.2 (SD: 26.7) (95% CI: 118.12, 138.27) μg] (P = 0.031). The emergence time and haemodynamic instability events were similar between AoA and CONOX. Conclusion: Both AoA and CONOX measure anaesthetic depth similarly. However, interpreting qNOX values requires caution, as the patient’s consciousness status influences them.